CRISPR/Cas9 Based Site-Specific Modification of FAD2 cis-Regulatory Motifs in Peanut (Arachis hypogaea L) - Neelakandan, Anjanasree K.; Wright, David A.; Traore, Sy M.; Chen, Xiangyu; Spalding, Martin H.; He, Guohao (Frontiers in Genetics, 2022)
Peanut (Arachis hypogaea L.) seed is a rich source of edible oil, comprised primarily of monounsaturated oleic acid and polyunsaturated linoleic acid, accounting for 80% of its fatty acid repertoire. The conversion of oleic acid to linoleic acid, catalyzed by Fatty Acid Desaturase 2 (FAD2) enzymes, is an important regulatory point linked to improved abiotic stress responses while the ratio of these components is a significant determinant of commercial oil quality. Specifically, oleic acid has better oxidative stability leading to longer shelf life and better taste qualities while also providing nutritional based health benefits. Naturally occurring FAD2 gene knockouts that lead to high oleic acid levels improve oil quality at the potential expense of plant health though. We undertook a CRISPR/Cas9 based site-specific genome modification approach designed to downregulate the expression of two homeologous FAD2 genes in seed while maintaining regulation in other plant tissues. Two cis-regulatory elements (CREs), the RY repeat motif and 2S seed protein motif in the 5UTR and associated intron of FAD2 genes are potentially important for regulating seed-specific gene expression. Using hairy root and stable germ line transformation, differential editing efficiencies were observed at both CREs when targeted by single gRNAs using two different gRNA scaffolds. The editing efficiencies also differed when two gRNAs were expressed simultaneously. Additionally, stably transformed seed exhibited an increase in oleic acid levels relative to wild type. Taken together, the results demonstrate the immense potential of CRISPR/Cas9 based approaches to achieve high frequency targeted edits in regulatory sequences for the generation of novel transcriptional alleles, which may lead to fine tuning of gene expression and functional genomic studies in peanut.